(untitled) (Scientific journal of the Fergana State University, 2025)
This paper examines an integrative method for studying language structures based on the interaction of two key aspects of the lexical system: paradigmatics and syntagmatics. Traditional analysis often isolates these two components, which leads to an incomplete understanding of their relationship and influence on the semantic and grammatical characteristics of language. The paper proposes a systematic approach that focuses on the dynamics of interaction between paradigmatic series (groups of words with common features) and syntagmatic links (combinations of words in the context of a sentence). The study includes examples from various languages, illustrating how this approach can enrich lexicography, translation theory, and language teaching. The article’s conclusions highlight the importance of integrated analysis for a deeper understanding of language structure and its functionality in communication.